Advancing the Valuation of Grassland Carbon Sinks: A Study of Three Calculation Methods for Fair Value Measurement - Ye Yan; Yujie Liu; Changbai Xiu; Yanli Tian; Muhammad Umer Arshad; Baoyin Dureng (SAGE Open)
Grassland ecosystems play a pivotal role in mitigating climate change via CO 2 sink. However, establishing robust methodologies for grassland carbon sink valuation remains complex scientific challenge. This study proposes an innovative application of fair value accounting principles to grassland carbon sink measurement, providing a multidimensional framework for ecological asset valuation. We develop a comprehensive theoretical foundation for fair value measurement through three analytical perspectives: cost-based, market-oriented, and income-driven valuation paradigms. Consequently, three valuation approaches are formulated: the Marginal Opportunity Cost (MOC) Method, Shadow Pricing (SP) Method, and Option Pricing (OP) Method. Through scenario-based comparative analysis, we demonstrate that methodological selection should be guided by carbon sink projects’ development stages and valuation objectives. Specifically, MOC excels in preliminary carbon pricing during project initiation phases, SP is optimal for mature primary markets with established transaction histories, while OP exhibits superior technical capabilities for projects’ future value estimation in secondary market transactions. This study provides practical insights for realizing ecological product value, advancing carbon market operations, and contributing to global climate change mitigation efforts.